Hubungan Dukungan Orang Tua dengan Social Skill pada Anak Speech Delay Usia 3-6 Tahun di Klinik Liliput Jakarta - Talitha Ula Sabilla, Pasya; Soesyasmoro, R. Asto (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Background: Speech delay in children is a common problem. A child is said to be late in speaking if his speech ability is below the proper level of development of the child's speech, and this has an impact on the child in developing his social skills (social skills). So it needs to be a serious concern for parents in supporting their children. Objectives: This research aims to determine the relation between parental support and social skill in children with speech delay aged 3-6 years at Liliput Clinic, Jakarta. Methods: This is a quantitative research with a cross-sectional study design and a correlational approach. Total Sampling was used as a data sampling technique for 35 samples. The research instrument used a questionnaire on parental support and social skills. Both data scales are ordinal and analyzed using the Kendall Tau test. Results: Based on the correlation test data analysis, the result is p = 0.006 which means that the p value < 0.05. So it can be concluded that Ha is accepted and Ho is rejected. This indicates that there is a relation between parental support and social skill in children with speech delay. Meanwhile, the correlation coefficient (r) is 0.337 which indicates that the relationship between the two variables is in the weak category and the direction of the correlation is positive. Conclusion: It can be concluded from this research that there is a relation between parental support and social skill in children with speech delay aged 3-6 years at Liliput Clinic, Jakarta. Keywords: Parental Support, Social Skill, Speech Delay. 1.0.0.20